Plan de negocio para la creación de una empresa de servicios informáticos en consultorios médicos y clínicas en la ciudad de Quito - Canchignia Terán, Diego Armando (2019)
The following business plan has the objective of analyze the financial viability for an informatic service company that will provide services to health professionals in Quito city, in clinics or consulting rooms in extended hours, focusing on attending SLA users that will allow accomplish chronograms and meet the established deadlines. The market niche is focused on health professionals registered in Agencia de la Calidad de los Servicios de Salud y Medicina Prepagada. The segment estimation is performed by convenience sampling done through 331 surveys using as polling tool Google Docs in order to reach the required surveys number and to have a register of favorable numbers for quantifying marketing prices and strategies. The assumptions used for the results in agreement with the sales projections reveals favorable values that allows to make viable a moderate investment. This makes unnecessary to fall in debt with a financial entity to start a microenterprise with a TIR of 40 percent with an investment refund period of 4.08 years.